Handbook of vascular motion - Cheng, Christopher P. (Academic Press, an imprint of Elsevier, 2019)
Handbook of Vascular Motion provides a comprehensive review of the strategies and methods to quantify vascular motion and deformations relevant for cardiovascular device design and mechanical durability evaluation. It also explains the current state of knowledge of vascular beds that are particularly important for the medical device industry. Finally, it explores the application of vascular motion to computational simulations, benchtop testing and fatigue analysis, as well as further implications on clinical outcomes, product development and business.